Alkaline proteases from a native bacillus sp alkaline strain (2006)
The effect of four nitrogen sources on the enzymatic activity of alkaline proteases, secreted by a native strain of Alkalophilic Bacillus sp, grown at different concentrations of LMF (Fermented Corn Liqueur) was evaluated. The growth of the strain is not affected by the inoculation pH of 7.0; 8.5 and 9.5; in contrast to the enzymatic activity and production of true protein, which had their best results at an initial pH of 8.5. At this pH two sources of organic nitrogen (yeast extract and peptone) and two inorganic (NH4Cl and NaNO3) were evaluated